2020
DOI: 10.1039/c9en01318k
|View full text |Cite
|
Sign up to set email alerts
|

What will happen when microorganisms “meet” photocatalysts and photocatalysis?

Abstract: In recent years, photocatalytic technology has been widely studied as an environmental restoration technology and energy production technology to solve the two crises of energy shortage and environmental pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 174 publications
0
31
0
Order By: Relevance
“…Almost any organic compounds can be photooxidized on TiO2 surface to CO2 and H2O [2,[5][6][7][8]. Viruses and bacteria can be destroyed over the photocatalytic surface as well [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Almost any organic compounds can be photooxidized on TiO2 surface to CO2 and H2O [2,[5][6][7][8]. Viruses and bacteria can be destroyed over the photocatalytic surface as well [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…2 ) that is harmful to bacteria. ROS attacks the cell membrane, and the coenzyme A on the cell membrane is hurt, resulting in inhibition of respiration dependent on the intact cell membrane, reduction or loss of cellular respiration activity, and eventually cause the control of the bacterial growth [65]. It was observed that the content of Zn in the ceramic coating increased by rising the concentration of ZnO nanoparticles within the electrolyte in Section 3.3.…”
Section: Antibacterial Performancementioning
confidence: 99%
“…Several studies have been reported on the photocatalytic inactivation of microorganisms. These photocatalyst can be used as good disinfectant against pathogens, which not only destroy them but also can be used sterilization 83–86. Therefore, more work is needed to address these specific requirements concerning various exiting, and challenging applications in bio‐medical science.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%